Réponses

2013-09-28T12:21:44+02:00
5x=2x-6
5x-2x=-6
3x=-6
x=-6/3  x=-2

2x+5=6x-7
2x-6x=-7-5
-4x=-12
4x=12  x=12/4  x=3

5-4x=20
-4x=20-5
-4x=15
x=-15/4

3x+5=10
3x=10-5
3x=5  x=5/3

-7x+3=4+x
-7x-x=4-3
-8x=1    x=-1/8

10x-15=7+20x
10x-20x=7+15
-10x=22    x=-22/10    x=-2,2
2013-09-28T12:22:08+02:00
b)  5x=2x-6
5x -  2x = -6
3x = -6
x = -2

c) 2x+5=6x-7
2x - 6x = -7 - 5
-4x = -9
x = 2,25

d) 5-4x=20
-4x = 20 - 5
-4x = 15
x = -3,75

f) -7x+3=4+x
-7x - x = 4 - 3
-8x = 1
x = -0,125

g) 10x-15=7+20x
10x - 20x = 7 + 15
-10x = 22
x = -2,2

Pour le e), je sais pas donc désolé.